Exploring Text and Icon Graph Interpretation in Students with Dyslexia: An Eye‐tracking Study. (16th January 2017) - Kim, Sunjung; Wiseheart, Rebecca
Abstract : A growing body of research suggests that individuals with dyslexia struggle to use graphs efficiently. Given the persistence of orthographic processing deficits in dyslexia, this study tested whether graph interpretation deficits in dyslexia are directly related to difficulties processing the orthographic components of graphs (i.e. axes and legend labels). Participants were 80 college students with and without dyslexia. Response times and eye movements were recorded as students answered comprehension questions about simple data displayed in bar graphs. Axes and legends were labelled either with words (mixed‐modality graphs) or icons (orthography‐free graphs). Students also answered informationally equivalent questions presented in sentences (orthography‐only condition). Response times were slower in the dyslexic group only for processing sentences. However, eye tracking data revealed group differences for processing mixed‐modality graphs, whereas no group differences were found for the orthography‐free graphs. When processing bar graphs, students with dyslexia differ from their able reading peers only when graphs contain orthographic features. Implications for processing informational text are discussed. Copyright © 2017 John Wiley & Sons, Ltd.